De novo mutation in the ARHGAP32 gene endorses the implication of GTPase-activating proteins (RhoGAP family) in idiopathic autism spectrum disorder - Cirnigliaro, Lara; Saccuzzo, Lucia; Marzà, Viviana; Randazzo, Martina; Perdichizzi, Maria; Romano, Corrado; Fichera, Marco; Rizzo, Renata; Barone, Rita (Frontiers in Psychiatry, 2026)
IntroductionARHGAP32 gene (Rho GTPase Activating Protein 32) encodes a Rho GTPase activating protein, which is vital for the regulation of synaptic plasticity and cytoskeletal dynamics. ARHGAP32 (11q24.3) has been implicated as a candidate gene for Autism Spectrum Disorder (ASD) in Jacobsen syndrome, where a 243-kb terminal deletion encompasses its locus. A unique patient with de novo (DN) likely gene-disruptive mutation of ARHGAP32 has been reported so far in the medical literature. The present study was undertaken to understand clinical, molecular, and neurobehavioral characteristics of ASD associated with a novel DN nonsense mutation in ARHGAP32.MethodsClinical characterization included basal and follow-up assessment with standardized measures and comorbidities diagnosis. Trio exome sequencing analyses (WES) and variants annotation were performed.ResultsWES analyses of a 6-year-old female patient with idiopathic ASD revealed DN heterozygous nonsense variant in ARHGAP32 (NM_001378024.1: c.610C>T; NP_001364953.1: p.(Arg204Ter). The variant is predicted to introduce a premature stop codon, resulting in either a truncated protein or activation of nonsense-mediated mRNA decay, ultimately leading to loss of function. The patient presented with normative growth parameters and cranial measurements, with no congenital morphological anomalies. A diagnosis of idiopathic ASD was made at age 2. Developmental delays were observed, notably language regression beginning at 18 months, mild intellectual disability, and restricted interests accompanied by repetitive motor and verbal behaviors. Significant hyperactivity and attentional difficulties were observed. Over time, she exhibited borderline non-verbal cognitive functioning, persistent speech impairment, and was subsequently diagnosed with comorbid Attention Deficit Hyperactivity Disorder.DiscussionThis study identifies shared neurobehavioral features of idiopathic Autism Spectrum Disorder (ASD) associated with de novo LoF mutations in ARHGAP32 and reinforces the involvement of RhoGAP family proteins in neurodevelopmental disorders. Taken together with previous evidence, our data support the role of ARHGAP32 as a candidate gene for ASD, expanding the genetic spectrum.